APPLICATION OF ADAPTIVE LEARNING MODEL TO FINE MOTOR DEVELOPMENT IN EARLY ELEMENTARY SCHOOL CHILDREN - Hendri (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to describe the application of adaptive learning models to the fine motor development of early elementary school students. This study uses a qualitative approach with a descriptive method. The subjects of the study were teachers and students of grade I at one of the State Elementary Schools. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study showed that teachers applied adaptive learning by adjusting learning activities to the motor abilities of each student. The learning activities used include tracing, scissors, scissors, gluing, and folding, which directly train eye-hand coordination and finger muscle strength. The application of adaptive learning has been proven to be effective in improving students' fine motor skills, which can be seen from the improvement of their work results and coordination of movements. Despite several obstacles, such as limited tools and differences in students' abilities, teachers are able to overcome them with creative strategies. Adaptive learning is becoming a relevant approach to apply in early grade education because it encourages the overall physical and cognitive development of students.